ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP DANA PIHAK KETIGA DI BANK PEMERINTAH DAN BANK SWASTA DI KALIMANTAN BARAT - B01108006, Inda Fitriyana (Jurnal Pembangunan dan Pemerataan, 2012)
This research named the analytic effect of domestic product regional bruto with the third side fund in government bank and any private bank in Kalimantan Barat. Problems that is to be want research is domestic product regional bruto with the third side fund in government bank and any private bank in Kalimantan Barat. The purpose to write this final assignment this research was to generally analyze the expansion of the third side fund and domestic product regional bruto to the third fund in government bank and private ini Kalimantan Barat. Research writer use deskriftif methode to see whats the context between free variabel (PDRB level) and varibel dependent then process it to reach the conclution. Research is regresi linier model. Beside, writer use statistic analye to examine relationship between variabel and R-square to see how much the presentage of product within up and down variation the third side fund. The result from this research for writer was to conclude that domestic product regional bruto and the third side fund is positive because third side fund in goverment and private bank mengalami peningkatan. More income advance, always a certain person seperate out little income for to save.